Shells of coconut and their durability against termite attack - Manuel, Daß; Wong, Andrew H.H; Unger, Wibke (The International Research Group on Wood Protection, 2015)
All tropical and subtropical areas of the Earth are inhabited by termites. In climates with moderate temperatures, they occur less frequently. Especially wood and non-wood materials that grows in tropical areas and used there in timber constructions and woodworking, wood durability and protection against termites should be researched. This paper reports findings from an experimental “AW011” laboratory forced- and choice- termite tests on the durability of shells of Coconut (Cocos nucifera L.) against termite attack by Reticulitermes santonensis de Feytaud to see if there could be any new use for them. Two reference tropical hardwoods were compared: Teak heartwood (Tectona grandis L.f.) as naturally durable and Jelutong sapwood (Dyera costulata Hook. f. (Miq.)) as non-durable wood. Furthermore, we compared with Beech (Fagus sylvatica L.). Pine sapwood (Pinus sylvestris L.) was the control for the tests. Overall from test varieties, termite mortality, visual rating and mass loss data, coconut shells and teak heartwood were comparably termite resistant. Jelutong and beech were rated moderately resistant while Pine was clearly susceptible among these non-durable woods.